Waste management for a Wet Market at Pasar Awam, Bota Perak / Syadiyatul A’frina Sofian and Nor Diana Aziz - Sofian, Syadiyatul A’frina; Aziz, Nor Diana (2023)
Waste management is systematic collection, transportation and disposal or treatment waste material that generate by human activities. Proper waste management is crucial for wet markets to avoid unpleasant smells, maintain cleanliness, and satisfy users. To ensure continued community satisfaction and support for wet markets, a study on consumer preferences and waste management is essential. The utilization of descriptive statistics to analyse the collected data allowed for a comprehensive overview of the satisfaction levels among wet market occupants. The findings revealed the varying degrees of satisfaction concerning different factors, such as the effectiveness of the dump place, the management of unpleasant smells, the efficiency of garbage collection, the functionality of the floor flow system, the presence of insects, and the performance of drainage systems. By employing a quantitative research approach and analysing the data using descriptive statistics, this study comprehensively evaluates the waste management practices at Pasar Awam, Bota Perak, with a specific focus on aspects.